P0074EXPANDING THE VARIABILITY OF THE ADPKD-GANAB CLINICAL PHENOTYPE: A NEW FAMILY OF ITALIAN ANCESTRY. (6th June 2020) - Delbarba, Elisa; Econimo, Laura; Dordoni, Chiara; Martin, Eva; Gnutti, Barbara; Savoldi, Gianfranco; Mazza, Cinzia; Dallera, Nadia; Scolari, Francesco; Izzi, Claudia
Abstract: Background and Aims: Causative GANAB mutations have been described in only 123 families, 98 diagnosed with late-onset mild ADPKD and 35 with ADPLD. We describe a new family with mild, late-onset ADPKD due to p. R839W GANAB mutation, previously reported in an ADPLD patient requiring liver transplantation. Method: Mutation analysis of PKD1, PKD2, GANAB genes was performed by targeted NGS analysis. To analyze GANAB gene we developed a custom panel of 11 kidney cystogenes (GANAB, PKDH1, TSC1, TSC2, UMOD, HNF1B, REN, OFD1, PARN, DNAJB11, SEC61A1) designed using Ion Ampliseq Designer. Sanger sequencing was performed in order to validate all the variants classified as pathogenic, likely pathogenic and VUS. Raw sequence data analysis, including base calling, demultiplexing, alignment to the hg19 human reference genome, was performed using the Torrent Suite Software version 5.5; the average depth of total coverage was set at 500X and for variant calls at minimum of 30X. Deletion and duplication analysis of PKD1 and PKD2 was performed using MLPA P351-C1 and P352-D1 probemixes, MRC-Holland. Results: Diagnosis of ADPKD was made in a 45-year old man during pre-surgical screening for umbilical and inguinal hernia repair. The patient's clinical course was characterized by several complications pertaining to the ADPKD spectrum: nephrolithiasis (20 yo); umbilical/bilateral inguinal hernia repair, hypertension and mild aortic root dilation (45 yo) and AKI due to ureteral obstruction (50 yo). Abdomen CT scan showed bilateral renal cysts (TKV 565 cc), nephrolithiasis, normal-sized liver with multiple cysts, and sigmoid colon diverticulosis. Renal function was normal (SCr 0.69 mg/dL, CKD-EPI 115 ml/min). In the index case, NGS and MLPA analysis of PKD1 and PKD2 genes did not detect variants. We then use the abovementioned multigene NGS panel and identified a missense heterozygous c.2515C>T (p.R839W) variant in the GANAB gene. Screening was then extended to family members. No family members displayed renal function impairment. Both the 80 yo mother and the 84 yo father were found to have multiple bilateral kidney cysts (HtTKV of 239 ml and 435 ml, respectively), no liver cysts were found in either of them. Parents segregation analysis identified the GANAB variant p.R839W in the mother and in the maternal aunt. The father tested negative for all the abovementioned cystogenes. Conclusion: we confirm that the renal phenotype caused by mutations in GANAB is very different from those due to mutations in PKD1 and PKD2, giving rise to a mild form of renal cystic disease, usually not progressing to ESRD. Despite the mild renal cystic burden, the index case showed a plethora of renal and extrarenal manifestations of ADPKD. The finding that patients with GANAB mutation can present with renal and liver cystic phenotype is intriguing, indicating a commonality between pathogenic background of two different inherited disorders, ADPKD and ADPLD. The missense GANAB mutation identified in our ADPKD family was first described in a pedigree reported by Porath et al. and diagnosed as ADPLD. This suggests that, beyond the effect of the shared mutation on GII subunit α, other modifier loci and environmental factors may influence the course of liver disease development and progression. Our study illustrates the important diagnostic role of a broader genetic testing, able to screen not only for PKD1 and PKD2 variants, but also for pathogenic variants in other cystogenes.